Providence in St. Albert the Great - Torrijos Castrillejo, David (Ciências da religião história e sociedade, 2016)
In these pages, we expose the main traits of St. Albert the Great’s doctrine of providence and fate, considered by Palazzo the keystone of his philoso-phical system. To describe it we examine his systematic works, primarily his Summa of Theology. His discussion follows clearly the guidelines of the Summa of Alexander of Hales, in order to delve into the set of proble-ms faced over the centuries by theological tradition. Albert also restates the reflections of different authors like Boethius or Saint John of Damascus but, in his Summa he incorporates to his reflections also the noteworthy book of Nemesius of Emesa, De natura hominis, which includes some pages on providence. Albert gives his personal solution to the complex questions of providence, destiny and contingency of the world. His con-ception of providence is developed in the frame of the creative power of the almighty God. God’s knowledge is necessary and inerrant and his pro-vidential purposes are infallible, but that does not mean that every event is necessary. He does not communicate His own proprieties to the creatures. In order to understand this problem, Albert recalls the notion of hypothe-tical necessity coined by Boethius in an Aristotelian framework and the difference between necessitas consequentis and necessitas consequentiae proposed by Alexander of Hales. He also develops his account of providen-ce, closely linked to the topic of fate. However, it would be exaggerated to deem his position deterministic.